Components Affecting Changes in Gross Profit and Net Profit Initiation - Rita Martini; Sulaiman Sulaiman; Kartika Sari; Kella Sauky; Sukmini Hartati (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
Financial problems are one of the very vital problems for the company in the development of business in all companies. The evaluation carried out by the company must begin with analyzing each data on the financial statements by comparing the post per post or period one with another. This evaluation uses the analysis of financial statements. Gross profit or profit is one of the main goals of the company in exploring its activities. The management always plans the amount of profit each period, which is determined through the targets to be achieved. The purpose of this study is to analyze and find out the causes of changes in gross profit and changes in net profit by comparing the income statements on CV. Mag Wilab Indonesia. The author uses secondary data, namely income statement. The final result analysis technique shows the causes of changes in gross profit and changes in net income with a comparison of three consecutive years. The results of the analysis using this comparison are that there is a change in gross profit marked by a decrease in gross profit in 2020 and an increase in gross profit in 2021. In addition, the next result is a decrease in net profit 2020 and 2021.